The Addition of Garciana xanthochymus on Beef Rendang: The Organoleptic Review - Zulfikar, Dikki; Akmal, Rifqi; Martinez-Gracia, Carmen (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
Rendang was a dish consumed regularly by the Minangkabau people and served at special events, becoming well-known worldwide. Garciana xanthochymus is a widespread species found in West Sumatra, and previous research has demonstrated its ability to preserve fresh fish. This study examined how adding various amounts of Garciana xanthochymus impacts the quality of Rendang, including color, shape, taste, aroma, and texture. This study employed an experimental approach, specifically the organoleptic test, to investigate the impact of varying quantities of Garciana xanthochymus (10, 20, 30, 40 grams). The collected data was analyzed using ANOVA with a one-factor wholly randomized design (CRD), consisting of four treatments replicated three times. As a result, there was no significant impact on the shape and aroma of Rendang. However, a significant effect was observed in the taste and color inside the meat, as well as the color and taste of the crust.